JURIDICAL REVIEW ON LAND ACQUISITION AND FREEING OF LAND RIGHTS FOR THE SHAKE OF PUBLIC INTEREST (Case Studi: Decision of Siak District Court No. 23/PDT.G/2017/PN.Sak) - Jonni Silitonga; Solistis Dachi; Rosnidar Sembiring (JURNAL PROINTEGRITA, 2019)
Procurement of land and land acquisition for the construction of the Pekan Baru-Dumai toll road in Siak Regency, is implemented in accordance with Law No. 2 of 2012 concerning the procurement of land and land acquisition for the public interest, the Public Works and Public Housing (PUPR) of the Republic of Indonesia, The National Land Agency of Siak Regency, and the Land Procurement Committee (P2T) determine compensation for landowners who have been released without consultation (the party entitled). Suwitno Lumban Batu and his colleagues filed a lawsuit against the Law, so that the formulation of the problem of the legal phenomenon is: 1) How to procure land and land acquisition rights in Siak Regency? 2) How are the laws and regulations on land acquisition and the release of land rights for public benefit? 3) How judicial judgments of the Siak District Court have been in conformity with the legal norms and principles of civil procedure law on the Decision of Article Number 23 / Pdt.G / 2017 / PN. Sak This research is a legal research. Legal research is carried out to find solutions to legal issues that arise, namely to provide a prescription of what should be the issue based on civil case verdict number 23 / Pdt.G / 2017 / PN.Sak. The type of data used includes primary data and secondary data. Methods of data collection through case chronology and copy of the Decision and library research both books, legislation, papers, previous research results, documents, etc.. The results of this study indicate that the discussion of land acquisition is an activity to obtain land by providing compensation to those who release or surrender land, buildings, and objects related to land where legal arrangements regarding land acquisition for public interest in Indonesia have undergone a process developments since the unification of the Basic Agrarian Law Number 5 of 1960 and Law number 12 of 2012 concerning land acquisition and the release of land rights in the public interest.